The Role of Lemon Grass (Cymbopogon citratus) in Improving Carcass Quality and Final Body Weight - Susanti, Susanti; S., Suraya Kaffi; P., Cintia Agustin; Santika , Luh Putu Nadya; Maharani, Nadia; M , Andre Meiditama (ABEC Indonesia, 2024)
Lemon grass (Cymbopogon citratus) has been valued for its aromatic and medicinal properties. This study explores itsrole in improving carcass quality and final body weight in broilers. The increasing global demand for high-quality meat productsnecessitates sustainable animal production systems. Traditional methods often use synthetic additives and antibiotics, raisingconcerns about food safety and environmental impact. Thus, natural alternatives like lemon grass, rich in essential oils,flavonoids, and phenolic compounds, are gaining attention. This experiment, conducted at Politeknik Negeri Lampung using fourthreatments and five replications and for further test using Duncan. The highest body weight and carcass percentage wereobserved in broilers with 1.5% lemon grass extract in drinking water. This study confirms lemon grass's potential as a naturalfeed additive, promoting sustainable and efficient livestock farming practices while improving meat production quality. Furtherresearch is recommended to optimize inclusion rates and understand long-term effects.